Effects of farmland conversion on the stoichiometry of carbon, nitrogen, and phosphorus in soil aggregates on the Loess Plateau of China - Zhang, Yi; Li, Peng; Liu, Xiaojun; Xiao, Lie; Shi, Peng; Zhao, Binhua (Geoderma, 2019)
Stoichiometry is an important indicator of the elemental balance in ecological interactions and processes. The impact of change in land use on soil aggregates, however, is uncertain. We studied the effect of the conversion of sloping farmland (SF) to woodland (WO), grassland (GR), shrub-land (SH), and terraced fields (TE) on aggregate structure, stability, and stoichiometry in 0–20, 20–40, and 40–60 cm soil layers. The proportion of large aggregates (>0.25 mm) in WO, GR, SH, and TE increased by 71, 66, 46, and 35%, respectively. The conversion favoured the transformation from aggregation of <0.25 mm aggregates to >0.25 mm aggregates. As an indicator of particle size distribution and aggregate ability, the soil fractal dimension decreased significantly (P < 0.05) as aggregate stability increased. Therefore, it was assumed that the ability of soil to resist damage by water erosion improved after conversion to WO. The C/N, C/P and N/P ratios ranged from 8.66 to 38.54, 3.54 to 10.25 and 0.16 to 0.76, respectively. The conversion of SF effectively increased the accumulation of organic carbon (C) and total nitrogen (N). Surface-soil C/P ratios differed significantly between SF and the converted land uses, and conversion significantly increased the surface-soil organic C content. Soil N/P ratio in the study area was low, mainly controlled by N, further confirming the lack of N in the study area. Land uses had no significant effect on C/N ratio, but forest and shrub land had improved N/P and C/P ratio. It showed that ecological construction could take a provocative role to improve soil structure and increase soil fertility. The results would provide a scientific basis for soil quality control and rational use of resources. •Contents of large particles and soil aggregates stability increase with farmland conversion.•Nitrogen tend to be the limited factor.•Land uses had no significant effect on C/N ratio, forest and shrub land obviously improved N/P and C/P ratio.